Theoretical References for an Accreditation Model From Evaluation and Quality Management - Zúñiga-Arrieta, Sandra (2022)
Introduction. This article focuses on constructing a theoretical framework for a model to evaluate the careers or programs associated with the National Accreditation System for Higher Education in Costa Rica (SINAES) to receive accreditation. SINAES is the official body to which the Costa Rican State, through law number 8256, granted the power to dictate quality policies in higher education institutions (IES) and accredit them, giving public faith to their quality. Objective. The research from which this proposal derives had the general objective of proposing epistemological theoretical foundations that would establish the evaluation model’s starting point for accreditation purposes that guides the agency’s actions. Method. The study was conducted from a qualitative approach that includes realities built around global and local epistemologies. In other words, the study was conducted based on complexity, taking the interpretation of texts as analysis units through content analysis. The texts were analyzed considering the different periods in which accreditation appears in the higher education scenario: 114 years of its emergence as a national phenomenon and the different discourses that impact Latin America and developments in Latin America. Analysis. Theoretically, the notions of evaluation, quality management, and the approach of accreditation and reaccreditation were taken as the starting point. Results. Proposing the conceptual bases from a vision that gives importance to both the evaluation process and the results, taking into account the study plan as the core of the curriculum. Conclusions. The primary result is a conceptualization of quality management, accreditation, and evaluation.